Testosterone and type 2 diabetes in men - Mazur, Allan; Westerman, Ronny; Werdecker, Andrea; Mueller, Ulrich (The aging male, 2014)
Abstract Objective: To assess from observational data if low testosterone in men is an independent risk factor for high fasting glucose (FG) and for a diagnosis of type 2 diabetes (T2D). Methods: Multivariate analysis of data from 991 male US Air Force veterans who completed six medical examinations over 20 years. Results: Low testosterone was moderately related to high FG, independent of age and obesity. Low testosterone is a very weak predictor of a diagnosis of T2D. Conclusions: In men, low testosterone is an independent risk factor for high FG, comparable to aging and obesity. Low testosterone is a weak predictor of a diagnosis of T2D.